DIGITAL MEDIA TO IMPROVE THE RECEPTIONAL LANGUAGE SKILLS OF CHILDREN AGED 4-5 YEARS AT NUR NABAWIY KINDERGARTEN, PASURUAN CITY - Lidya Nur, Auliyani (USN Kolaka, 2023)
Receptive language skills in early childhood need to be developed before developing speaking skills (expressive language). This research aims to improve the receptive language skills of children aged 4-5 years with the research object being group A students of Nur Nabawiy Kindergarten, Pasuruan City, totaling 14 children. The research used was a type of Classroom Action Research (PTK) which was carried out over two cycles. Data collection techniques are observation and interviews. Based on the research conducted, it can be concluded that there is an increase in children's receptive language skills through activities using digital media. The results of research in group A at Nur Nabawiy Kindergarten, Pasuruan City experienced an increase in each cycle.